Experiential Other-Directness: To What Does it Amount? - León, Felipe (Tidsskrift for Medier, Erkendelse og Formidling, 2013)
Drawing upon contributions by Husserl, Stein, and other classic phenomenologists, some theorists in the field of social cognition have advanced the idea that we often have direct and experiential access to another person’s mind. This claim challenges the assumption, widespread in Theory of Mind approaches to social cognition, that other minds are essentially hidden behind psychologically meaningless patterns of observable behaviour. In this paper, I discuss three models for articulating the phenomenological idea of an experiential other-directness and suggest the superiority of one of them. Keywords: social cognition, phenomenology, empathy.